The Pembentukan Pneumatologis dalam Kepemimpinan Kristen melalui Peran Roh Kudus sebagai “Competency Enabler" - Gunarto, Hendra; Marbun, Purim (PNEUMATIKOS: Jurnal Teologi Kependetaan, 2025)
Abstract: This study examines the formation of Christian leadership from a pneumatologically perspective, emphasizing the role of the Holy Spirit as a competency enabler. Employing a qualitative approach through literature review, the research explores how the Holy Spirit guides, equips, and empowers Christian leaders. The Holy Spirit imparts vision, cultivates divine abilities and knowledge through spiritual gifts, while also shaping the leader’s character through the fruit of the Spirit and enhancing relational capacities with God and others. The findings indicate that active spiritual formation by the Holy Spirit significantly contributes to the integrity, effectiveness, and sustainability of leadership within the ecclesial context. The practical implication of this study underscores the necessity of developing a holistic leadership training model that integrates pneumatological principles into church leadership curricula, aiming to produce competent, impactful, and adaptive Christian leaders responsive to the dynamics of contemporary ministry.